MEG/EEG Group Analysis With Brainstorm - Tadel, François; Bock, Elizabeth; Niso, Guiomar; Mosher, John C.; Cousineau, Martin; Pantazis, Dimitrios; Leahy, Richard M.; Baillet, Sylvain (Frontiers in Neuroscience, 2019)
Brainstorm is a free, open-source Matlab and Java application for multimodal electrophysiology data analytics and source imaging [primarily MEG, EEG and depth recordings, and integration with MRI and functional near infrared spectroscopy (fNIRS)]. We also provide a free, platform-independent executable version to users without a commercial Matlab license. Brainstorm has a rich and intuitive graphical user interface, which facilitates learning and augments productivity for a wider range of neuroscience users with little or no knowledge of scientific coding and scripting. Yet, it can also be used as a powerful scripting tool for reproducible and shareable batch processing of (large) data volumes. This article describes these Brainstorm interactive and scripted features via illustration through the complete analysis of group data from 16 participants in a MEG vision study.